Risk factors for neonatal death in Sleman Regency: analysis of Sleman HDSS data for 2015-2020 - Yanti, Windra; Wahab, Abdul; Wahdi, Amirah Ellyza (BKM Public Health and Community Medicine, 2023)
Purpose: This study aims to address the critical issue of neonatal mortality, which remains a significant public health concern, particularly in low and middle-income countries where 75% of neonatal deaths occur within the first week of life, and approximately one million newborns die within the first 24 hours, influenced by various maternal and neonatal risk factors. Methods: This was an observational study that used a longitudinal design. The sample size was 824 respondents born and living in Sleman, DIY. The purpose of this study was to identify risk factors for neonatal death. Data analysis used descriptive analysis, bivariable, and multivariable. Results: Multivariable analysis showed that the risk factors associated with the incidence of neonatal death were the mother's age (OR=143.4; CI: 16.92-1215.36), baby's weight (OR=15.24; CI: 1.8-112.92), and history of abortion (OR=9.27 CI; 1.7-50.33). Conclusion: Based on the results of the study, maternal age is the most influential risk factor for the incidence of neonatal death in Sleman Regency. Mothers who are pregnant and give birth aged <18 years have a risk of 143.4 times higher for neonatal death compared to women who are pregnant and give birth aged 18-34 years. Therefore it is necessary to increase education and empower women to prevent early marriage.